Contribution of Production Unit Experience, Soft Skill, and On The Job Training to Student’s Competency and its Effect to The Work Readiness - Dyah Ayu Pradnya Paramitha; Nizwardi Jalinus (invotek, 2020)
The goal of this research was to know contribution between exogenous variable to the endogenous variable. Exogenous variable was practical of production unit (X1), soft skill (X2), and on the job training (X3), whereas endogenous variable was student’s competency (Y) and work readiness (Z). This research used quantitative approach with survey method. The research population was students in the Culinary Study Program at Batam Tourism Polytechnic. Sample in this research was 122 respondents that determined by using proportional random sampling technique. Data collection technique used questionnaire and documentation, data analysis technique that used in this research was path analysis. Test in the path analysis was divided into two groups, simultaneously and individually. The research result showed that there was significant contribution between practical experience of production unit, soft skill, and on the job training to the student competence for 99%, and significant contribution between practical experience of production unit, soft skill, on the job training, and student competence to the work readiness for 99,2%.